ANALYSIS OF WEB-BASED PROMOTION MEDIA DEVELOPMENT IN TOBA FILM COMMISSION - Delima Sitanggang; Cristian Andika Tarigan; Agustinus Lumban Raja (INFOKUM, 2021)
Nowadays where technology has grown rapidly, the Internet also enlivens the biggest revolution in technological advancement where the internet can facilitate in accessing various information. The Internet is widely used by creative workers to provide information so that it can be known by everyone who uses the internet. The problem in the current research is that the Toba Film Commission is deadlocked in informing the data owned to the public because the Toba film commission does not yet have a container or place to spread the information accurately. The data collection techniques used in this study are Library Studies, Observations, Interviews, And methods used to analyze this problem there are qualitative methods. with the analysis of the development of media promotion of web-based Toba film commission, this can help promote tourism and scouting locations with the help of google maps to get the desired information and facilitate film actors in finding the necessary equipment such as cameras, lighting, tripods, etc. in North Sumatera, especially in the Lake Toba area. With the creation of this website, the public can easily dig up information related to tourism and scouting in the North Sumatera area.